1995
DOI: 10.1021/bi00017a025
|View full text |Cite
|
Sign up to set email alerts
|

The Human Dopamine D5 Receptor Gene: Cloning and Characterization of the 5'-Flanking and Promoter Region

Abstract: Genomic and overlapping cDNA clones encompassing the entire 5'-untranslated region of the human D5 receptor gene were cloned and sequenced. Comparison of these human D5 receptor genomic and cDNA clones revealed the presence of two exons separated by a small and variably sized intron (of either 179 or 155 bp). We have determined that the major site of transcription initiation of the D5 gene is 2125 bp upstream from the translational initiation start site. The region 5' to the transcription initiation site lacke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 27 publications
2
28
0
1
Order By: Relevance
“…However, recently a number of investigations have reported some highly regulated genes to have TATA-less promoters (23). GPCRs observed to have GC-rich, TATA-less promoters include D 1 , D 2 , and D 5 dopaminergic and the ␤ 1 adrenergic receptor (18,(24)(25)(26)(27). All of these promoters have also been observed to contain Sp1 sites, although the transcriptional requirement of Sp1 has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently a number of investigations have reported some highly regulated genes to have TATA-less promoters (23). GPCRs observed to have GC-rich, TATA-less promoters include D 1 , D 2 , and D 5 dopaminergic and the ␤ 1 adrenergic receptor (18,(24)(25)(26)(27). All of these promoters have also been observed to contain Sp1 sites, although the transcriptional requirement of Sp1 has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Differential distribution of receptor mRNAs also characterizes mammalian D 1A and D 1B receptors. D 1A receptors are present at very high levels in the striatal and olfactory regions, whereas D 1B receptors are expressed mainly in the hippocampus and cortex in the human and also in the parafascicular nucleus of the thalamus in rat (29,36,37). The localization of the D 1A and D 1B receptors seems to be essentially nonoverlapping in mammals.…”
Section: Cloning and Sequencing Of Four Distinct D 1 -Like Receptormentioning
confidence: 96%
“…However, recent studies have demonstrated that some highly regulated genes, including immediate early genes, developmentally regulated genes, and tissue-specific genes, also have promoters that lack TATA boxes (25). Genes encoding several other G-protein-coupled receptors, including D 1 (26,27), D 2 (28), and D 5 (29) dopaminergic and ␣ 1B (30) and ␤ 1 (31,32) adrenergic receptors, also have GC-rich promoters that lack TATA boxes. These promoters also contain several putative Sp1 binding sites, although the requirement of Sp1 binding for transcription of these genes is yet to be determined.…”
Section: Figmentioning
confidence: 99%